Distinct Cell Transcriptomic Landscapes Upon Henipavirus Infections - Chen, Mingyue; Tachedjian, Mary; Marsh, Glenn A.; Cui, Jie; Wang, Lin-Fa (Frontiers in Microbiology, 2020)
Hendra virus (HeV) and Cedar virus (CedV) are henipaviruses, which fall into the Paramyxoviridae family of single-stranded, negative-sense RNA viruses. HeV is classified as a Biosafety Level-4 (BSL-4) agent, as it is highly pathogenic and is often fatal to humans. To date, no HeV prevention or treatment methods for human are available. In contrast, previous experimental infection studies have suggested that CedV is non-pathogenic. Flying foxes (pteropid bats) in Australia are the natural reservoirs of both viruses, but the cellular responses of bats to these viral infections remain unclear. Here, we infected bat and human cells with these viruses. We then examined the total transcriptomic landscapes of the cells at 6 or 24 hours post infection. Unexpectedly, despite the close phylogenetic relationship between HeV and CedV, there was a dramatic difference in cellular gene expression patterns in response to the two different infections. It is likely that minor differences in the phosphoprotein (P) gene coding strategy between the two viruses cause the observed incongruence in host transcriptomic divergence and viral lethality. This study greatly expands our understanding of the pathogenic mechanisms of henipaviruses.